Assessing the efficacy and impact of a personalised smoking cessation intervention among type 2 diabetic smokers: study protocol for an open-label randomised controlled trial (DISCGO-RCT). Issue 11 (19th November 2020) - Clair, Carole; Augsburger, Aurélie; Birrer, Priska; Locatelli, Isabella; Schwarz, Joelle; Greub, Gilbert; Zanchi, Anne; Jacot-Sadowski, Isabelle; Puder, Jardena J
Abstract : Introduction: Few studies have assessed the efficacy of smoking cessation interventions in individuals with type 2 diabetes, but interventions adapted to the specific needs of this population are warranted. The aim of this study is to assess the efficacy of a smoking cessation intervention in a population of smokers with type 2 diabetes and to measure the metabolic impact of smoking cessation. Methods and analysis: The study is an open-label, randomised control trial. Participants recruited from a sanitary region of Switzerland will be randomly allocated to either the intervention or the control arm. The intervention group will have four individual counselling sessions over 12 weeks. Trained research nurses will conduct the behavioural intervention, using motivational interviews and addressing diabetes and gender specificities. The control group will have one short counselling session at baseline and will be given written information on smoking cessation. Both groups will have a follow-up visit at 26 and 52 weeks. Demographic and medical data will be collected at baseline and follow-up, along with blood and urine samples. The primary study outcome is continuous smoking abstinence validated by expired-air carbon monoxide from week 12 to week 52. Secondary study outcomes are continuous and 7-day point prevalence smoking abstinence at 12 and 26 weeks; change in motivation to quit and cigarette consumption; and change in glycosylated haemoglobin levels, body weight, waist circumference and renal function after smoking cessation. In a subsample of 80 participants, change in stool microbiota from baseline will be measured at 3, 8 and 26 weeks after smoking cessation. Ethics and dissemination: Ethical approval has been obtained by the competent ethics committee (Commission cantonale d'éthique de la recherche sur l'être humain, CER-VD 2017–00812). The results of the study will be disseminated through publications in peer-reviewed journals and conference presentations. Trial registration numbers: ClinicalTrials.gov NCT03426423 and SNCTP000002762; Pre-results.